2021
DOI: 10.1016/j.exphem.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: sensitive detection of residual lymphoproliferative disease by NGS and clonal rearrangements—how low can you go?

Abstract: Malignant lymphoproliferative disorders collectively constitute a large fraction of the hematological cancers, ranging from indolent to highly aggressive neoplasms. Being a diagnostically important hallmark, clonal gene rearrangements of the immunoglobulins enable the detection of residual disease in the clinical course of patients down to a minute fraction of malignant cells. The introduction of next-generation sequencing (NGS) has provided unprecedented assay specificity, with a sensitivity matching that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
10
1
Order By: Relevance
“…Even though the focus on high sensitivity of MRD detection is often emphasized in commercially available assays, the true sensitivity of any MRD assay is determined by the number of evaluated cells 20 and the desired sensitivity is not reached for a large number of samples evaluated in MRD studies (eg, 40% of samples reported by Wood et al). 6 It is equally important to maintain a very high specificity and implement sufficient checks to avoid false-positive results that would lead to therapy intensification and may be the cause of serious treatmentrelated toxicity, especially in pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the focus on high sensitivity of MRD detection is often emphasized in commercially available assays, the true sensitivity of any MRD assay is determined by the number of evaluated cells 20 and the desired sensitivity is not reached for a large number of samples evaluated in MRD studies (eg, 40% of samples reported by Wood et al). 6 It is equally important to maintain a very high specificity and implement sufficient checks to avoid false-positive results that would lead to therapy intensification and may be the cause of serious treatmentrelated toxicity, especially in pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…While NGS can have discrepant results because of interlaboratory differences, variable performance of the available technologies, and sitespecific sample collection procedures, strict standardization will ensure consistent and comparable results. Ongoing efforts are aimed at reaching uniform timing of BM collection and sample processing and at defining the amount of DNA input, number of replicates, number of sequencing reads, and With the aim of implementing MRD in MM everyday patients' care, careful standardization, consistent sensitivity, reproducibility, and affordability of NGS-MRD assays will be fundamental (1,75,76).…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing efforts are aimed at reaching uniform timing of BM collection and sample processing and at defining the amount of DNA input, number of replicates, number of sequencing reads, and sequence similarity thresholds for determining clonotypes. With the aim of implementing MRD in MM everyday patients’ care, careful standardization, consistent sensitivity, reproducibility, and affordability of NGS-MRD assays will be fundamental ( 1 , 75 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRD was detected in 4 SCPs, whereas 13 samples were MRD negative. The collection of about 3 million autograft cells theoretically required for a high sensitivity of 10 −6 [16] , which is often the intended detection level of recent studies, can be challenged by the availability of patient material and sample processing. In our study, the content of rearranged IgH sequences of B cells was calculated from the number of total reads and spike-in reads generated by 100 control cells.…”
Section: Discussionmentioning
confidence: 99%